(untitled) (Research, Society and Development, 2020)
Among the main neurodegenerative diseases resulting from the senescence process in the population, Alzheimer stands out, which results from the destruction or injury of neurons in brain regions involved with cognitive functions. With the evolution of Alzheimer’s disease, areas related to the performance of basic functions are affected. Thus, it is known that although there is no established treatment for the cure or reversal of Alzheimer’s degeneration, non-pharmacological interventions that promote better care and well-being for the elderly, such as playful activities and memorization practices represent a modality capable of reducing or temporarily stagnate the progress of symptoms. Based on this, this study aims to describe the use of recreational activities in elderly people with Alzheimer’s in a long-term care institute for the elderly, characterized as descriptive with a qualitative approach, in the form of an experience report on the theoretical-practical experience developed in a shelter for the elderly by health academics, adhering to the principles of the Methodology of problematization by the Arco de Maguerez. As main results it was noted that the elderly showed themselves to be idle and shy, as they did not practice physical exercises and did not interact with the local people. Activities were carried out that generated group interaction and were accessible to everyone to awaken the desire for physical exercise and recreational activities, providing well-being and assistance in health promotion. The action achieved the established objectives, promoting therapeutic stimuli associated with the motor and cognitive part of these people. The activities carried out provided an active participation of the elderly women in the studied place. Thus, the importance of scientific promotion within this theme is emphasized, as well as the participation of the health academic to acquire skills and competences aimed at the public.